1974
DOI: 10.1038/bjc.1974.189
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Growth of Tumour Cells in Acutely Inflamed Tissues

Abstract: Summary.-Acute inflammatory reactions were induced in rats by the intravenous injection of cellulose sulphate (CS) or The mechanisms which may be responsible for the nonspecific growth promoting effects of inflammatory reactions induced by various types of tissue injury on tumour induction and growth are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…In our view, a demise of emigrant cells could be equally well attributed to their escape from the conditioning effect of tumour-cell-derived trophic substances, which "pool" in the micro-environment of a high-cell-density parent-tumour-cell inoculum. It is cogent also, that many tissue homogenates and preparations of fibrinogen cause inflammation, which has been shown to be conducive to survival, take and clonogenic growth of seeded tumour cells, even in animals treated with anti-coagulant drugs in high dosages to inhibit blood clotting (van den Brenk et al, 1974). However, we have shown that the swelling of the foot caused by LI cells differs in important respects from the typical acute exudative phase of an inflammatory reaction to an injurious agent.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In our view, a demise of emigrant cells could be equally well attributed to their escape from the conditioning effect of tumour-cell-derived trophic substances, which "pool" in the micro-environment of a high-cell-density parent-tumour-cell inoculum. It is cogent also, that many tissue homogenates and preparations of fibrinogen cause inflammation, which has been shown to be conducive to survival, take and clonogenic growth of seeded tumour cells, even in animals treated with anti-coagulant drugs in high dosages to inhibit blood clotting (van den Brenk et al, 1974). However, we have shown that the swelling of the foot caused by LI cells differs in important respects from the typical acute exudative phase of an inflammatory reaction to an injurious agent.…”
Section: Discussionmentioning
confidence: 73%
“…This disadvantage suffered by small V-cell inocula in maintaining concentrations of growth factor in their micro-environment which are required to ensure cell survival and growth is clearly greatest when single cells are inoculated and each cell is required to clone for proliferative growth to be initiated. The survival and clonogenic growth of i.v.-injected tumour cells in the lungs of rats are greatly increased by simultaneous injection of LI cells, if the recipient animal is young (recently weaned) and actively growing, or if reactive hyperplasia of target tissues has been induced by injurious stressor agents, irrespective of age of rat (van den Brenk et al, 1974). We have attributed these effects of age and tissue stress on tumour colonyforming efficiency (CFE) to enhanced local elaboration of trophic agents by the tumour bed in states of rapid innate or reactive growth; an effect analogous to the Revesz effect produced by LI cells, which actively growing normal tissue exercises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Bennett, 1979(Bennett, , 1982(Bennett, , 1989. Furthermore, some PGs are involved in inflammation, which has a variable effect on tumour spread, a small inflammatory reaction causing enhancement and a large one causing inhibition (Van den Brenk et al, 1974).…”
Section: Resultsmentioning
confidence: 99%
“…Susceptibility to tumour growth (measured in terms of tumour-colony-forming efficiency, CFE) in the lung and other organs, however, is markedly increased in grown rats by the induction of states of topical or systemic stress (van den Brenk et al, 1976a). Thus, local X-irradiation of the lungs (van den Brenk et al, 1973b;Milas and Withers, 1970) injection of rats with adrenergic drugs, inflammatory agents (cellulose sulphate, Compound 48/ 80) or chemical convulsants, and physical restraint of rats (van den Brenk et al, 1974) markedly increased tumour OFE.…”
mentioning
confidence: 99%